2016
DOI: 10.1044/2015_jslhr-l-15-0052
|View full text |Cite
|
Sign up to set email alerts
|

Narratives in Two Languages: Storytelling of Bilingual Cantonese–English Preschoolers

Abstract: The results of this study have implications for speech-language pathologists who collect narratives in Cantonese and English from bilingual preschoolers. The results suggest that there is a possible transfer in narrative abilities between the two languages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 57 publications
2
10
1
6
Order By: Relevance
“…The results are consistent with Kang (2012) but contrast with Rezzonico et al (2016). Similar to the current study, Kang found that Korean macrostructure was not related to Korean-English bilingual children's English macrostructure when microstructure abilities were controlled.…”
Section: Cross-language Relations Between English Macrostructure and supporting
confidence: 91%
See 3 more Smart Citations
“…The results are consistent with Kang (2012) but contrast with Rezzonico et al (2016). Similar to the current study, Kang found that Korean macrostructure was not related to Korean-English bilingual children's English macrostructure when microstructure abilities were controlled.…”
Section: Cross-language Relations Between English Macrostructure and supporting
confidence: 91%
“…Kang (2012) examined 5-to 6-year-old Korean-English bilinguals and found that English microstructure measures predicted children's production of English macrostructure; however, children's production of Korean macrostructure was not a significant predictor of English macrostructure when controlling for English narrative microstructure measures. Contrary to Kang's findings, Rezzonico et al (2016) examined 4-to 5-year-old Cantonese-English bilingual children and found that Cantonese macrostructure did predict English macrostructure after controlling for English microstructure measures. The mixed findings may be due, in part, to differences in the participants' language dominance, a possibility that is discussed below.…”
contrasting
confidence: 79%
See 2 more Smart Citations
“…Even if the studies are aimed at school teachers, these activities can also include preschool teachers' methods of working in the preschool, as children need meaningful literary practices at an early state. In the preschool storytelling activities are highlighted for multilingual children as a good way of creating meaning and developing language awareness Rezzonico et al, 2016). Cummins et al (2005) consider that multilingual children who are given the opportunity to process linguistic concepts in their different languages parallel with one another and to transfer them from one to the other will be supported in the development of their biliteracy, that is, the children's literacy development in more than one language.…”
Section: Something Described By Grøver Aukrustmentioning
confidence: 99%